PCR en tiempo real para la detección cuantitativa de ADN bovino en piensos vegetales - Marín de la Torre, Irene (Revista Complutense de Ciencias Veterinarias, 2007)
A real-time polymerase chain reaction (PCR) approach using SYBR green detection system has been developed for the quantitative detection of bovine tissues in feedstuffs and food. The method combines the use of bovine-specific primers, that amplify a 84 bp fragment of the mitochondrial 12S ribosomal RNA gene, and universal primers that amplify a 140 bp fragment of the nuclear 18S ribosomal RNA gene from eukaryotic DNA. The 18S rRNA primers are used as endogenous control for the total content of PCR-amplifiable DNA in the sample. The specificity of the primers was tested against 18 animal species including mammals, birds and fish, as well as 6 plant species. Analysis of experimental bovine tissues/oats mixtures demonstrated the suitability of the assay for the detection of bovine DNA in mixtures containing as low as 0.1% of bovine tissues. The performance of the method was not affected by severe heat treatment (up to 133ºC for 20 min at 300 kPa).